MANAJEMEN DI SANGGAR AFNALYA DANCE COMPANYDI KOTA MANNA KABUPATEN BENGKULU SELATAN - Fitria Nopita Sari; Astuti, Fuji (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
The aim of this research is to uncover the management system run by the Afnalya Dance Company. This research employs a qualitative approach with a descriptive method. The research is located at the Afnalya Dance Company, Manna City. The focus of the research is the management system implemented at the studio. Data collection techniques are conducted through observation, interviews, documentation, and literature studies. Data analysis is carried out through the processes of data reduction, data presentation, and conclusion drawing. The results of the research show that the management of the studio encompasses planning activities in the form of training programmes and performances in both the short and long term. The process of organisation is evident in the clearly formed organisational structure along with detailed division of tasks. Activities are driven through giving direction, motivation, and direct guidance to the members of the group. The supervisory function is carried out through routine evaluations of the discipline and skill development of members. Additionally, the group also implements project management, marketing strategies, and financial management that are conducted simply yet efficiently. In terms of music provision, the group does not yet have internal musicians and still relies on external parties. Overall, the management system of the group prioritises the principles of togetherness and participation, thereby supporting the sustainability and development of the group within the community.